La Revue Nouvelle : les questions de société en débat (Bruxelles: Thomas Lemaigre)
"Bibliotheek Camille HuysmansPeriodiciteit : maandelijksRedactie : Boulevard Général Jacques 126 - 1050 Brussel - 02/6403107 - redaction@revuenouvelle.be"